Factors Affecting Adoption of Improved Sesame Technologies in Some Selected Areas in Bangladesh: An Empirical Study - Miah, M A Monayem; Afroz, Sadia; Rashid, M A; Shiblee, S A M (The Agriculturists, 2016)
This study was undertaken to assess the adoption level as well as farmers attitude towards cultivating Bangladesh Agricultural Research Institute (BARI) developed improved sesame varieties and its technology management as well. Keeping this view in mind, primary data were collected from major three sesame growing areas of Bangladesh namely, Comilla, Jessore, and Faridpur districts. A total of 540 samples, selected using stratified random sampling method, were interviewed using pre-tested and structured questionnaires. Results reveal that the improved sesame seed adoption level is around one fifth of the total sesame cultivation. The adoption of relating technologies regarding input usage and agronomic practices also depicted similar characteristics due to not taking up recommended improved seed package. Analysis also showed that availability of family labor, application of improved seeds and monitoring and supervision of extension personnels have significant contribution on improved seed adoption levels. Although farmers opined that they would be adopting the improved sesame seeds in the upcoming fostering season in view of expanding yields, profits, labor productivity and efficient cultivation. However, many farmers have articulated their concern about unavailability of improved sesame seeds at the farm levels is a major barrier about adopting improved sesame technology. The Agriculturists 2015; 13(1) 140-151